Postgraduate study in national academic systems (experience of Germany and USA) - S. A. Dushina; N. A. Ashcheulova (Vestnik MGIMO-Universiteta)
This paper investigates the German and USA system of post-graduate training, with a special focus on the institutional features of the postgraduate courses. Based on the German statistical databases, it undertakes a detailed analysis of sociodemographic characteristics for doctoral students (рromovierende), the types of employment, the financing of projects. This paper will also highlight the peculiarities of mobility processes in the framework of the national post-graduate courses. The authors take note that the key points for the organization of scientific research are the public recognition of science and social status of scientists.